The Involvement of Peripheral and Brain Insulin Resistance in Late Onset Alzheimer’s Dementia - Folch, Jaume; Olloquequi, Jordi; Ettcheto, Miren; Busquets, Oriol; Sánchez-López, Elena; Cano, Amanda; Espinosa-Jiménez, Triana; García, Maria Luisa; Beas-Zarate, Carlos; Casadesús, Gemma; Bulló, Mónica; Auladell, Carme; et al. (Frontiers in Aging Neuroscience, 2019)
Nowadays, Alzheimer's disease (AD) is a severe sociological and clinical problem. Since it was first described, there has been a constant increase in its incidence and, for now, there are no effective treatments since current approved medications have only shown short-term symptomatic benefits. Therefore, it is imperative to increase efforts in the search for molecules and non-pharmacological strategies that are capable of slowing or stopping the progress of the disease and, ideally, to reverse it. The amyloid cascade hypothesis based on the fundamental role of amyloid has been the central hypothesis in the last 30 years. However, since amyloid-directed treatments have shown no relevant beneficial results other theories have been postulated to explain the origin of the pathology. The brain is a highly metabolically active energy-consuming tissue in the human body. It has an almost complete dependence on the metabolism of glucose and uses most of its energy for synaptic transmission. Thus, alterations on the utilization or availability of glucose may be cause for the appearance of neurodegenerative pathologies like AD. In this review, the hypothesis known as Type 3 Diabetes will be evaluated by summarizing some of the data that has been reported in recent years. According to published research, the adherence over time to low saturated fatty acids diets in the context of the Mediterranean diet would reduce the inflammatory levels in brain, with a decrease in the pro-inflammatory glial activation and mitochondrial oxidative stress. In this situation the insulin receptor pathway would be able to fine tune the mitochondrial biogenesis in neuronal cells, regulation the ATP/ADP intracellular balance, and becoming a key factor involved in the preservation of the synaptic connexions and neuronal plasticity. In addition, new targets and strategies for the treatment of AD will be considered in this review for their potential as new pharmacological or non-pharmacological approaches.